PENATAAN KAWASAN PERUMAHAN DAN PERMUKIMAN DALAM UPAYA PENINGKATAN SARANA DAN PRASARANA DI DESA LOMBA KECAMATAN LAMALA KABUPATEN BANGGAI - Mulyaningtyas, Wishni Lestarini; Anwar, Chairil; Rusli, Rusli (Katalogis, 2020)
This research aims to find out the levels of availability, needs and amount of budget allocation needed to fulfill facilities in the context of effort to structure residential area to support the socio-economic life of the people in Lomba village. This was a descriptive qualitative research with a survey method. The research findings show that the level of availability of residential facilities in Lomba village is available but still need to be improved the quality such as environmental roads, drainage, markets and housing with a total budget needed of Rp. 12,317,400,000. The availability of adequate facilities will encourage increased community production so as to encourage rural economic growth.